The phosphatidylinositol 3‐kinases (PI3K) inhibitor GS‐1101 synergistically potentiates histone deacetylase inhibitor‐induced proliferation inhibition and apoptosis through the inactivation of PI3K and extracellular signal‐regulated kinase pathways. (25th July 2013) - Bodo, Juraj; Zhao, Xiaoxian; Sharma, Arishya; Hill, Brian T.; Portell, Craig A.; Lannutti, Brian J.; Almasan, Alexandru; Hsi, Eric D.
Summary: Previously, we showed that inhibition of the protein kinase C β (PKCβ)/AKT pathway augments engagement of the histone deacetylase inhibitor (HDI)‐induced apoptosis in lymphoma cells. In the present study, we investigated the cytotoxicity and mechanisms of cell death induced by the delta isoform‐specific phosphatidylinositide 3‐kinase (PI3K) inhibitor, GS‐1101, in combination with the HDI, panobinostat (LBH589) and suberoylanilide hydroxamic acid (SAHA). Lymphoma cell lines, primary non‐Hodgkin Lymphoma (NHL) and chronic lymphocytic leukaemia (CLL) cells were simultaneously treated with the HDI, LBH589 and GS‐1101. An interaction of the LBH589/GS‐1101 combination was formally examined by using various concentrations of LBH589 and GS‐1101. Combined treatment resulted in a synergistic inhibition of proliferation and showed synergistic effect on apoptotic induction in all tested cell lines and primary NHL and CLL cells. This study indicates that interference with PI3K signalling dramatically increases HDI‐mediated apoptosis in malignant haematopoietic cells, possibly through both AKT‐dependent or AKT‐ independent mechanisms. Moreover, the increase in HDI‐related apoptosis observed in PI3K inhibitor‐treated cells appears to be related to the disruption of the extracellular signal‐regulated kinase (ERK) signalling pathway. This study provides a strong rational for testing the combination of PI3K inhibitors and HDI in the clinic.